Prevalence of Gingival Recession and its Relationship to Past Orthodontic Treatment in Nepalese Young Adults - Dhami, Bhageshwar; Shrestha, Priti; Gupta, Sujaya; Shrestha, Sujita; Shrestha, Rabindra Man (Orthodontic Journal of Nepal, 2016)
Introduction: Gingival recession is characterized by apical migration of gingival margin from the cementoenamel junction. Prevalence varies from 3-100%, and appears to be lower in younger age groups. Objective: To determine the prevalence and severity of gingival recession in young adult Nepalese population and to assess the relationship between brushing technique, smoking habit and past orthodontic treatment with gingival recession. Materials & Method: A cross-sectional study was carried out among 160 healthy patients (age 18-25 years) with routine dental examinations and information regarding age, smoking habit, oral hygiene habits, brushing technique and past orthodontic treatment. Clinical examination included visible gingival inflammation, visible dental plaque, and gingival recession. SPSS version 20 was used to analyze the data. Chi-Square test was used to evaluate relationships between the variables. Result: Out of total participants; gingival recession was found in 21.3%, gingivitis in 40% and plaque in 20%. The prevalence, extent, and severity of recession were correlated with past orthodontic treatment. There was association between gingivitis, past orthodontic treatment and smoking with gingival recession. Conclusion: Orthodontic patients must undergo regular oral hygiene performance and periodontal maintenance in order to maintain healthy gingival tissue during active orthodontic therapy. The combined orthodontic-periodontic interdisciplinary approach could be effective in these situations. Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.7-11